Cost efficient management of complex financial energy trading systems: Knowledge-based blockchain technique - Qi Liu; Pengbo Wan; Fen Chen; Weiting Li (Journal of Innovation & Knowledge (JIK), 2023)
Industry 4.0 has led to the growth of smart cities utilizing the Internet of Things (IoT). Wireless sensor network (WSN) has drawn considerable interest as an important element of the IoT. The Energy Internet (EI) is growing in importance as a significant component of constructing the intelligent city, especially in terms of its reliability and security. EI is moving in a new direction of energy trading advancement where distributed energy transaction models are replacing the conventional centralized layout. Blockchain technology, which is the underlying support, has gained interest as a result of its benefits, namely integrity, and nonrepudiation. Privacy disclosure, despite the benefits, is a concern for many blockchain-enabled trading layouts. The paper presents encryption according to the cryptographic text properties as the main scheme for reconstructing the dealing layout in order to resolve the issue in the electricity market. In particular, the blockchain energy trade plan with privacy (BETPWP) has been developed to manage the distributed transaction. Transaction arbitration in ciphertext form is employed for achieving precise access control. As a result of this method, the transaction layout could be made considerably more secure and reliable, as well as maximizing the security of private data. BETPWP also proposes a credibility-enabled equity proof consensus method that would significantly improve operational performance. A study of security and the test assessment of the suggested method are performed in order to demonstrate its effectiveness.
Keywords: 650; Blockchain; Encryption; Energy market trading; Privacy and efficiency enhancement; Smart power system